The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/biology6020026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Specific scFvs against Total Adiponectin for Diagnostic Purposes

Abstract: Adiponectin is one of the most abundant adipokines secreted from adipose tissue. It acts as an endogenous insulin sensitizer and plasma concentrations are inversely correlated with obesity and metabolic syndrome. A decrease in plasma adiponectin levels normally indicates increased hormonal activity of the visceral lipid tissue, which is associated with decreased insulin sensitivity. It may therefore be considered a valuable biomarker for elucidating the underlying deteriorations resulting in type 2 diabetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Adiponectin is an insulin-sensitizing protein secreted from adipose tissue, and has been shown to improve glucose tolerance and insulin resistance in humans (Devasia et al, 2017). Many studies showed that metabolic syndrome, insulin resistance and obesity were associated with lower adiponectin (Pervanidou et al, 2013;Wilton et al, 2017). Menale et al (2016) have declared an inverse association between adiponectin and BPA urinary levels independently in obese children; they explained that exposure to BPA leads to down-regulation of adiponectin expression.…”
Section: Introduction mentioning
confidence: 99%
“…Adiponectin is an insulin-sensitizing protein secreted from adipose tissue, and has been shown to improve glucose tolerance and insulin resistance in humans (Devasia et al, 2017). Many studies showed that metabolic syndrome, insulin resistance and obesity were associated with lower adiponectin (Pervanidou et al, 2013;Wilton et al, 2017). Menale et al (2016) have declared an inverse association between adiponectin and BPA urinary levels independently in obese children; they explained that exposure to BPA leads to down-regulation of adiponectin expression.…”
Section: Introduction mentioning
confidence: 99%